2018
DOI: 10.1038/s41598-017-18838-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of poled state in P(VDF-TrFE)/(Pb,Ba)(Zr,Ti)O3 composites probed by temperature dependent Piezoresponse and Kelvin Probe Force Microscopy

Abstract: Polarized states of polymer/inorganic inclusion P(VDF-TrFE)-(Pb,Ba)(Zr,Ti)O3 composites are studied at the nanoscale using both piezoresponse force microscopy (PFM) and Kelvin probe force microscopy (KPFM). It has been shown that inorganic inclusions can be visualized using KPFM due to a discontinuity of the surface potential and polarization at the interface between the inclusions and the polymer matrix. The temperature evolution of the PFM and KPFM signal profiles is investigated. Softening of the polymer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The PFM amplitude and phase images are shown in Figure 6a,b for the samples shown, respectively, in Figure 5c,d. As a matter of fact, despite the small d 33 values of 1 pm/V for the F-PVDF film, the domain polarization process was highly robust, as even the domain irregularities were kept at exactly the same places after 24 h. Again, our un-poled thin films showed piezoelectric coefficients values in good agreement with previous results reported in the literature for poled films at high temperature [32][33][34][35][36][37][38][39][40] without metallic nano-inclusions. In addition, in our case the PFM phase switching occurred at a lower electric field (50 MV/m) than the typical values reported in the literature (100-150 MV/m).…”
Section: Recoveries and Robustness Of Local Piezoelectric Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…The PFM amplitude and phase images are shown in Figure 6a,b for the samples shown, respectively, in Figure 5c,d. As a matter of fact, despite the small d 33 values of 1 pm/V for the F-PVDF film, the domain polarization process was highly robust, as even the domain irregularities were kept at exactly the same places after 24 h. Again, our un-poled thin films showed piezoelectric coefficients values in good agreement with previous results reported in the literature for poled films at high temperature [32][33][34][35][36][37][38][39][40] without metallic nano-inclusions. In addition, in our case the PFM phase switching occurred at a lower electric field (50 MV/m) than the typical values reported in the literature (100-150 MV/m).…”
Section: Recoveries and Robustness Of Local Piezoelectric Propertiessupporting
confidence: 90%
“…In addition, although there have been a considerable number of works measuring their dielectric, piezoelectric, and magnetoelectric properties that undeniably support the idea of their optimization being directly linked to the dispersion of the magnetic nano-inclusions, currently, there is still an important lack of the characterization of the local electroactive and magnetostrictive properties. Several studies have shown the local piezoelectric properties of PVDF-TrFE copolymer neat films [33] as well as hybrid films based on the artificial mixing of the PVDF and copolymer phase with non-magnetic nano-phases (e.g., CNTs, ZnO, (Pb,Ba)(Zr,Ti)O 3 , graphene) [34][35][36][37][38][39]. Only very recent studies [40,41] have shown the possibility of using the magnetic phase organization inside the polymer matrix to improve the local PFM properties under the application of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…solar cells [37][38][39] or fuel cell [40][41][42] and lithium ion battery materials. 30,32,43,44 Detailed analysis of interfaces in polymer-particle composites, however, are mainly limited to analysis of charge distribution at carbon-based particles like carbon nanotubes, 45 fullerenes 46 or piezoelectric materials 47 embedded in isolating polymers. Polymerparticle hybrid electrolytes for lithium ion batteries have not been addressed so far to the best of the author's knowledge.…”
Section: State Of the Art And Theoretical Considerationsmentioning
confidence: 99%
“…In general, composites based on PVDF or its copolymer with trifluoroethylene P­(VDF–TrFE) with embedded electrically active inorganic fillers show exceptional promise for applications in various devices such as capacitors, actuators, sensors, and contact switches. The films of the P­(VDF–TrFE) polymer itself offer relatively good mechanical compliance, ferroelectric, pyroelectric, and piezoelectric properties compared with other polymers . P­(VDF–TrFE) copolymer with the molar ratio of 70/30 is one of the most studied compositions.…”
Section: Introductionmentioning
confidence: 99%